Pola Pembinaan Akhlak Remaja Di Dusun Kwadungan Krincing Desa Kwadungan Gunung Kecamatan Kledung Kabupaten Temanggung - Milka Noviyatus Solikhah; Maryono Maryono; Salis Irvan Fuadi (Pusat Riset dan Inovasi Nasional, 2023)
This research is located in Kwadungan Krincing Hamlet, Kwadungan Gunung Village, Kledung District, Temanggung Regency. This study aims to (1) find out the various patterns of youth moral development in Kwadungan Kringing Hamlet, Kwadungan Gunung Village, Kledung District, Temanggung Regency. (2) Explain the supporting and inhibiting factors in the process of fostering adolescent morals.Field research using a qualitative descriptive approach is located in Kwadungan Kringungan Hamlet, Kwadungan Gunung Village, Kledung District, Temanggung Regency. Data collection techniques in this study included direct observation, in-depth interviews, and required documentation.Based on the analysis of this research data, the results that can be concluded from the researcher are that the supporting factors are. There are various patterns in moral development, namely by threats/punishments, talking from heart to heart, giving rewards/gifts, and giving direct examples. Factors that hinder and support the pattern of moral development, namely environmental factors, mindset factors, factors of habits that have been carried out long ago.